Analisis Sosial Ekonomi dalam Pola Kemitraan Agribisnis antara Petani Mitra dengan PT. Bengkulu Sawit Lestari di Kecamatan Kedurang Ilir - Begi Aryes; Herri Fariadi; Evi Andriani (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
This research aims to analyze the palm oil agribusiness partnership pattern implemented by PT. Bengkulu Sustainable Palm Oil in Kedurang Ilir District, South Bengkulu, along with its impact on farmer partners. The research method was carried out descriptively with a qualitative approach, using primary data through in-depth interviews and secondary data from related documents. Respondents consisted of 440 partner farmers and 2 companies selected purposively. The research results show that the partnership pattern implemented is the Plasma Core Pattern (IP), where PT. Bengkulu Sawit Lestari acts as the core that guides and purchases the results of plasma farmers. The conflicts that occurred were relatively low, with the majority of partner farmers stating that there were no physical or significant conflicts. From an economic aspect, partner farmers produce an average of 4,038 kg of FFB per month, with a selling price of Rp. 1,948 per kilogram, resulting in net income of Rp. 5,512,443 per month after deducting costs. In conclusion, this agribusiness partnership succeeded in increasing farmer productivity and income, despite deficiencies in training and financial reporting by the company. It is recommended that companies and farmers jointly write written sanctions in agreements, increase training, and provide monthly financial reports to strengthen partnership relations.